Use of a bio-electronic device comprising of targeted dual neuromodulation of the hepatic and celiac vagal branches demonstrated enhanced glycemic control in a type 2 diabetic rat model as well as in an Alloxan treated swine model - Waataja, Jonathan J.; Nihalani, Raj K.; Honda, Chris N.; Billington, Charles J. (Frontiers in Neuroscience, 2022)
Background There is an unmet need for new type 2 diabetes treatments providing improved efficacy, durability and customized to improve patient’s compliance. Bio-electronic neuromodulation of Vagus nerve branches innervating organs that regulate plasma glucose, may be a method for treating type 2 diabetes. The pancreas has been shown to release insulin during Vagus stimulation. The hepatic vagal branch, innervating the liver, has been shown to decrease glucose release and decrease insulin resistance following ligation. However, standalone stimulation of the Vagus nerve has shown mixed results and Vagus nerve ligation has undesirable effects. Little is known; however, of the effect on plasma glucose with combined neuromodulation consisting of stimulation of the celiac branch innervating the pancreas with simultaneous high frequency alternating current (HFAC) blockade of the hepatic branch. This study tested the effects of this approach on increasing glycemic control in rat a model of type 2 diabetes and Alloxan treated swine. Materials and methods Zucker obese (fatty) male rats (ZDF fa/fa) were used as a model of type 2 diabetes as well as glucose intolerant Alloxan treated swine. In ZDF rat experiments glycemic control was accessed with an intravenous glucose tolerance test during HFAC-induced hepatic branch block with concurrent celiac stimulation (HFAC + stimulation). In swine experiments glycemic control was accessed by an oral glucose tolerance test during HFAC + stimulation. Insulin measurements were taken prior to and following swine experiments giving insight into beta cell exhaustion. Histopathology was conducted to determine safety of HFAC + stimulation on Vagal branches. Results Zucker rats demonstrated a significant improvement to an intravenous glucose tolerance test during HFAC + stimulation compared to sham. There was no significant difference from sham compared to hepatic vagotomy or celiac stimulation. In Alloxan treated swine, when subjected to HFAC + stimulation, there was a significant improvement in glycemic control as measured by an improvement on oral glucose tolerance tests and a decrease in fasting plasma glucose. Insulin responses were similar prior to and following HFAC + stimulation experiments. Histopathology demonstrated healthy swine Vagus nerves. Conclusion Electrical blockade of the hepatic Vagus branch with simultaneous stimulation of the celiac Vagus branch may be a novel, adjustable and localized approach for a treatment of type 2 diabetes.